Regional pericarditis with reciprocal ECG changes mimicking inferior ST-elevation myocardial infarction (STEMI): A case report - Rahman, Gilang Mauladi; Alsagaff, Mochammad Yusuf (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Acute pericarditis is generally presented with a chest pain and a diffuse ST-segment elevation in ECG. Focal ST-segment elevation due to localised inflammation of pericardium in regional pericarditis could resemble ST-elevation myocardial infarction (STEMI). A case in this study was a 30-year-old man in emergency room as a surgery resident experiencing recently acute typical chest pain. He had a history of smoking without other cardiovascular disease risk factors. ECG immediately was conducted, and it revealed ST-segment elevation in an inferior lead with reciprocal ST-segment depression in aVL, which was typical for an inferior STEMI. Primary PCI was conducted, and it surprisingly revealed a normal coronary artery. Serial serum cardiac biomarkers found a normal cardiac troponin-I level (<0.001 mcg/L) and did not significantly change after serial examinations. We treated the patient as a suspect of coronary spasm with calcium-channel blockers and nitrates. After three days of hospitalization, the patient was discharged from the hospital, and he planned to get cardiac magnetic resonance (CMR). The CMR was conducted after seven days of the discharge, and it revealed a loculated pericardial effusion leading to regional pericarditis. The patient was treated with empirical NSAIDs for three weeks. Clinical and echocardiographic evaluation after the treatment showed an excellent result. A presence of focal ST-segment elevation with reciprocal ST-segment depression was generally consistent with the STEMI, but this case was an exception. Although rare, regional pericarditis can be a differential diagnosis in a patient with acute chest pain with a focal ST-segment elevation.